Melanoma in pregnancy: multidisciplinary treatment management and outcome - Francesca Romana Grippaudo; Giulia Ruggeri; Paola De Simone; Monia Di Prete; Guglielmo Tellan; Elena Rita Govoni; Emilia Migliano (Dermatology Reports)
Pregnancy-associated melanoma affects both maternal and fetal health. This study aims to demonstrate how a specialized center and a multidisciplinary approach can provide the best outcomes. From January 2006 to September 2023, a bicentric observational study was conducted at the Plastic Surgery Department of Policlinico Umberto I, Sapienza University of Rome, and at the Plastic and Regenerative Surgery Department of the San Gallicano Dermatological Institute IRCCS, Rome, Italy. Out of 6800 melanoma cases, twenty pregnant women were selected: thirteen underwent only wide local excision (WLE), while seven also had sentinel node biopsy (SLNB). All preoperative, operative, and postoperative steps were performed to ensure the safety of mothers and fetuses. Two patients developed metastases, with one fatality from hepatic metastases. The overall survival rate at 5-year follow-up was 86%, and 72% for advanced stages and disease-free patients. No maternal or fetal complications related to surgery were reported. Additionally, early deliveries at 7 and 8 months did not result in neonatal complications. Surgical treatment should be conducted in centers with both surgeons and gynecologists, and special care is necessary for procedures on pregnant women. Based on our experience, pregnancy does not seem to be a negative prognostic factor for melanoma.